Analisis Kasus Kekerasan Anak Terhadap Orang Tua di Bekasi - Gunawan, Ade; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Domestic violence cases committed by children against their biological mothers have attracted public attention, especially when similar incidents occur in the Bekasi area on Sunday, June 22, 2025. These acts of violence reflect serious disturbances in family relationships, weak emotional control of the perpetrators, and the possible involvement of external factors such as substance abuse or social pressure. This study aims to analyze the causal factors, background of the perpetrators, and social responses to cases of child abuse against biological mothers in Bekasi. The method used in this study is a descriptive qualitative approach with case studies, referring to media data, social observations, and family criminology theory. The results of the study indicate that the violence was triggered by a combination of prolonged family conflict, weak moral education from an early age, and minimal psychosocial support in the surrounding environment. The victim's mother suffered physical injuries and psychological trauma, while the perpetrator showed signs of emotional disturbance and impulsive behavior. Handling this case requires cross-sector collaboration, from law enforcement officers, forensic psychologists, to family protection institutions. This study recommends strengthening character education, family counseling services, and early reporting systems to prevent similar violence in the future.